DETERMINANTS OF NATURAL RESOURCES BASED MICROENTERPRISES PERFORMANCE IN INDIA’S WESTERN HIMALAYAN REGION: A NAÏVE BAYES CLASSIFIER ANALYSIS - Bahuguna, Ina; Kumar, Ujjwal; Arunachalam, Kusum; Shridhar, Vijay; Sharma, Archana (International Journal of Small and Medium Enterprises, 2023)
The natural resources-based Microenterprises are the major part of the economy of the western Himalayan region of Uttara hand, India, as the region is predominantly covered with reserved forests. The present study evaluates the performance of Microenterprises and the factors affecting it in the region using the primary data enumerated from 110 microenterprises sampled under four major categories of microenterprises, viz, agro and allied, Animal and allied, handicrafts and handlooms, and miscellaneous. The Naïve Bayes classifier approach has been applied to evaluate the performances (Loss-making, breakeven, profit-making, or high-profit making) of these microenterprises based on their performance determining factors such as ease of raw material availability, level of training received, technological advancement, and the extent of market knowledge, and also on the type of ownership and the employee’s number. The Naïve Bayes classification accuracy on the training dataset was 100%, while accuracy on the test dataset ranged from 93% to 100%. The results revealed that agro-based microenterprises have a greater probability (0.67) of making a profit/high profit, while animal product-based microenterprises have a high probability of running into losses. A higher level of Market Knowledge contributes to a high probability (0.89) of making high profits. The higher level of technology and training provides greater chances/probability (0.72, 0.72) of making high profits. Self-help groups (SHGs) have shown a better probability of making profits. The study suggests promoting SHGs in the region, wider dissemination of the market knowledge (marketing strategy), and leveling up the training/technology of the microenterprise. JEL Classification Codes: O13, L26.